Electrical and thermal characterization of YBCO coated conductors for resistive fault current limiter applications - Baldan, Carlos A. [UNESP]; Shigue, Carlos Y.; Ruppert Filho, Ernesto (Institute of Electrical and Electronics Engineers (IEEE), 2015)
Electrical and thermal characteristics of Yttrium Barium Copper Oxide (YBCO) coated conductors (CCs) with different architectures, with and without stabilizer layers, in resistive fault current limiters (RSFCLs) have been widely studied. In this study, the recovery of the superconducting state under different conditions (no-load and under load) is analyzed for subsequent fault current limitation. Test of modular RSFCL using commercial coated conductor with and without the assistance of an air-core power reactor was carried out. Shunt-assisted quench tests were investigated and measurements have been performed in short samples employed in the construction of modular unit with 6 stacks of 0.7-m length of 12-mm width YBCO CC tapes. Using the pulsed current method (PCM), the quench current (from Ic up to 3 × Ic) for a time period from 16.6 to 80 ms was applied to evaluate the temperature and recovery time, by the power losses, generated after the second quench in sequence. The RSFCL operates in a distribution grid protected by a recloser switch with intervals of 300 ms, 900 ms, and 1.2 s. For these time intervals, it is necessary to verify if full recovery behavior happens.
Keywords: current limiting ratio; recovery time; Superconducting fault current limiter; YBCO coated conductor